The effects of anesthesia with a combination of intramuscular xylazine-diazepam-ketamine on heart rate, respiratory rate and cloacal temperature in roosters - Mostachio, Giuliano Q. [UNESP]; de-Oliveira, Luciana D. [UNESP]; Carciofi, Aulus C. [UNESP]; Vicente, Wilter R. R. [UNESP] (Blackwell Publishing, 2008)
Objective To examine the anesthetic effects of a xylazine-diazepam-ketamine (XDK) combination in roosters.Study design Prospective experimental trial.Animals Six healthy white Leghorn roosters weighing 2.03 +/- 0.08 kg.Methods Each rooster was pre-medicated with xylazine (3 mg kg(-1), IM) and after 15 minutes anesthesia was induced with a diazepam (4 mg kg(-1)) and ketamine (25 mg kg(-1)) combination injected into the pectoral muscles. Heart and respiratory rates were recorded before anesthesia and every 15 minutes after induction for 165 minutes. Cloacal temperature was measured before and 15 minutes after pre-medication and every 75 minutes thereafter during anesthesia. Quality of induction and recovery were scored subjectively; duration of loss of righting reflex, abolition of response to a painful stimulus and palpebral reflex were also recorded.Results Intramuscular injection of xylazine smoothly induced loss of the righting reflex within 3-4 minutes. Loss of response to a painful stimulus occurred at 13.1 +/- 2.9 minutes (mean +/- SD) after the administration of the D-K combination, and lasted for 63.0 +/- 5.3 minutes. Roosters anesthetized with this combination had a significant decrease in heart and respiratory rates and cloacal temperature. The recovery period lasted for up to 4 hours (227.5 +/- 15.4 minutes). Quality of recovery was satisfactory for four roosters but excitation was noted in two birds.Conclusions and clinical relevance The XDK combination was a useful anesthetic technique for typhlectomy in roosters. Nevertheless this drug combination should be used with caution and cardiopulmonary parameters monitored carefully. Under the conditions of this experiment it was associated with a decreased cloacal temperature and prolonged recoveries.
Keywords: Anesthesia; avian; diazepam; Ketamine; Roosters; xylazine